Isolation and Characterization of Listeria monocytogenes Phage vB_LmoH_P61, a Phage With Biocontrol Potential on Different Food Matrices - Stone, Edel; Lhomet, Antoine; Neve, Horst; Grant, Irene R.; Campbell, Katrina; McAuliffe, Olivia (Frontiers in Sustainable Food Systems, 2020)
The high mortality rate associated with Listeria monocytogenes as well as its ability to adapt to the harsh conditions employed in food processing have ensured that this pathogen has become a significant concern in the ready-to-eat food industry. Lytic bacteriophages are viruses that hijack their bacterial host’s metabolic mechanisms as a means to grow and replicate, subsequently leading to host cell death due to lysis. With emerging concerns related to the increasing numbers of antibiotic-resistant pathogens, bacteriophages may act as a suitable biocontrol alternative. This study reports the biological and genomic characterisation of the broad host range Listeria monocytogenes phage vB_LmoM_P61 and its potential application for the reduction of Listeria monocytogenes in artificially contaminated foods. Phage vB_LmoM_P61 is a virulent bacteriophage belonging to the family Myoviridae and has a genome size of 136,481 bp. The lytic spectrum of vB_LmoM_P61 was investigated and the genomic basis for its observed serotype specificity (1/2a, 1/2b, 1/2c, 4b, 4e and 6a) investigated using comparative genomics. Treatment of artificially contaminated milk with vB_LmoM_P61 resulted in a significant reduction in Listeria monocytogenes numbers when stored at 8 °C and 12 °C for the duration of the shelf life. The results also show that vB_LmoM_P61 reduced the growth of L. monocytogenes when baby spinach was artificially contaminated and stored at 8 °C and 12 °C. Preliminary studies were carried out on other solid food matrices such as fresh pesto and hummus, however vB_LmoM_P61 was inactivated in these matrices and significantly reduced in concentration. The research findings indicate that biocontrol of Listeria monocytogenes with vB_LmoM_P61 may offer a safe and environmentally friendly approach for the reduction of Listeria monocytogenes numbers in some ready-to-eat foods.